Hypoxia Modulates Effects of Fatty Acids on NES2Y Human Pancreatic β-cells - Šrámek, Jan; Němcová-Fürstová, Vlasta; Polák, Jan; Kovář, Jan (International journal of molecular sciences, 2019)
Saturated fatty acids (FAs) induce apoptosis in the human pancreatic NES2Y β-cell line while unsaturated FAs have nearly no detrimental effect. Moreover, unsaturated FAs are capable of inhibiting the pro-apoptotic effect of saturated FAs. Hypoxia is also known to have deleterious effects on β-cells function and viability. In the present study, we have tested the modulatory effect of hypoxia on the effect of FAs on the growth and viability of the human pancreatic NES2Y β-cells. This study represents the first study testing hypoxia effect on effects of FAs in pancreatic β-cells as well as in other cell types. We showed that hypoxia increased the pro-apoptotic effect of saturated stearic acid (SA). Endoplasmic reticulum stress signaling seemed to be involved while redistribution of FA transporters fatty acid translocase/cluster of differentiation 36 (FAT/CD36) and fatty acid-binding protein (FABP) do not seem to be involved in this effect. Hypoxia also strongly decreased the protective effect of unsaturated oleic acid (OA) against the pro-apoptotic effect of SA. Thus, in the presence of hypoxia, OA was unable to save SA-treated β-cells from apoptosis induction. Hypoxia itself had only a weak detrimental effect on NES2Y cells. Our data suggest that hypoxia could represent an important factor in pancreatic β-cell death induced and regulated by FAs and thus in the development of type 2 diabetes mellitus.
Keywords: caspases; beta-buňky; NES2Y; Cell Line; signální transdukce; hypoxie; Hypoxia; Fatty Acids; kaspasy; Signal Transduction; Cell Proliferation; fatty acid transporters; hypoxia-inducible factor 1α; stres endoplazmatického retikula; Caspases; Humans; Endoplasmic Reticulum Stress; biologické markery; hypoxia; ER stress; viabilita buněk; Cell Survival; Insulin-Secreting Cells; proliferace buněk; pancreatic β-cells; mastné kyseliny; buněčné linie; Biomarkers; fatty acids; apoptosis; lidé